Laxity index measurement on stress radiographs obtained using the Vezzoni-modified Badertscher distension device technique: repeatability and reproducibility in a large cohort of dogs - Sassaroli, Sara; Gallorini, Francesco; Roggiolani, Francesco; Salvaggio, Alberto; Vallefuoco, Rosario; Pratesi, Andrea; Fordellone, Mario; Campagnoli, Elisa; Palumbo Piccionello, Angela (Frontiers in Veterinary Science, 2025)
IntroductionThe Vezzoni-modified Badertscher distension device (VMBDD) technique is a radiographic method used to assess hip joint laxity, and it is widely used across Europe. While the intra-observer and inter-observer variability of the laxity index (LI) measured on stress radiographs obtained using the VMBDD technique has been reported, it has never been evaluated in a large cohort of patients. The study aims to assess the repeatability and reproducibility of the LI measured on stress radiographs obtained using the VMBDD technique in a large cohort of dogs.MethodsStress radiographs obtained using the VMBDD method were analyzed for medium to large breed dogs, aged between 4.5 and 6 months and presented between 2021 and 2024 for screening of hip dysplasia. The LI for each hip was blindly measured by three observers with different levels of experience. Significant intra- and inter-observer variability was evaluated to assess the repeatability and reproducibility of the LI, respectively. Statistical testing was performed, and a p-value of <0.05 was considered statistically significant. Inter-observer and intra-observer intraclass correlation coefficients (ICCs) were evaluated.ResultsA total of 195 stress radiographs (390 hip joints) were included. The inter-observer ICC showed moderate agreement (ICC = 0.55, 95% CI 0.50–0.59). Estimated marginal means (EMMeans) indicated that Observer 3 consistently provided higher LI values compared to Observers 1 and 2 across all time points (e.g., at T1: 0.484 vs. 0.410 and 0.438, p < 0.001 for Observer 1 vs. Observer 3). The repeatability within each observer was excellent for all three observers (Observer 1: ICC = 0.94, 95% CI 0.93–0.96; Observer 2: ICC = 0.99, 95% CI 0.99–0.99; Observer 3: ICC = 0.95, 95% CI 0.94–0.96).ConclusionIn-house evaluation of the LI on stress radiographs obtained using the VMBDD technique showed that it was a highly repeatable procedure but a moderate reproducible measurement due to a systematic upward bias by an observer with less experience. Nevertheless, the mean differences could be considered negligible in a clinical setting due to their low impact on the definitive diagnosis.